Medical Assistance in Dying for Multiple Chemical Sensitivities: A System Failure? - Straube, Sebastian; Els, Charl; Fan, Xiangning (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2022)
We were astonished to read a recent media news item about a 51-year-old woman in Ontario who was offered and accepted medical assistance in dying (MAID) because she was experiencing multiple chemical sensitivities, also known by its preferred diagnostic term, idiopathic environmental intolerance (IEI). Reportedly, she could not access appropriate housing. We find this concerning, as providing MAID to individuals with refractory IEI symptoms on the basis of housing unavailability implies that there were no better management options available. This case should prompt ethical reflection on whether our supports for the most vulnerable enable them to maintain basic human dignity, and whether systemic societal action in other ways could better support people with IEI.